Pelatihan Pembuatan Pojok Cita-cita sebagai Upaya Meningkatkan Motivasi Siswa SDN 019 Desa Lipatkain Utara Untuk Menggapai Cita-Cita - Silvia Permatasari; Raja Bani Firmansyah; Afifah Damayani Aprilia; Nurul Puspita Sari; Tiara Tiara; Melva Nurjanah; Yogi Saputra; M. Hidayatullah D; Jumi Jumi; Rizky Maulana Van Reza; Rahma Yulia Ningsih (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
Ideals are someone's wishes in the future. However, not a few of the children do not know about their goals in the future. Insights about ideals must be instilled in every child so that they can plan their future better. The UNRI Fold Kain Utara KKN team carried out several methods starting from finding information about how far the children's knowledge was in recognizing their goals, then continued with explaining their goals, then looking at the development of knowledge about their goals, then the team continued by confirming their goals. the ideals of each child, and finally pasting the ideals they wrote in a medium called the ideal corner. As a result, the children better understand what their goals are after being explained by the team. They gain knowledge about what goals are and have an idea for future goals. Children become more specific to set goals. This is because they feel they have been encouraged by the team on the importance of setting goals. The result, from previously not being able to find goals in the future, to being able to determine goals that are in accordance with the wishes and abilities of each child.Keywords: ideals, ideal corner, motivation